Comparison of Hexane, Methanol, and Their Mixtures as Solvents for Microalgae Lipid Extraction by Hydrodynamic Cavitation - Martomo Setyawan; Siti Jamilatun; Muhammad Nufail Syafii; Resyaldi Pratama (Universitas Ahmad Dahlan, 2020)
The process of producing biodiesel from microalgae as an effort to solve energy problems is currently constrained by the negative energy balance, which requires more energy to produce than the heating value of biodiesel. The lipid extraction assisted by hydrodynamic cavitation requires less energy extraction than the heating value of biodiesel. The effort to increase the energy efficiency of the hydrodynamic cavitation extraction process is to find a solvent that has a low boiling point. This study aims to improve energy efficiency by using a solvent mixture of hexane and methanol, which has a low boiling point. The results showed that the methanol hexane mixture with a volume ratio of 4:1 gave the lowest mixture boiling point of 51.2 Â°C with a yield of 3.28% g lipid/ g dry microalgae. The process runs at a temperature of 30 Â°C with a driving pressure of 5 kg/cm2, with an extraction energy requirement of 2 kJ/g of lipids. This process is feasible to be developed to produce biodiesel from microalgae with a positive energy balance.